Answer:
An =4^(n-1)
Step-by-step explanation:
hello :
the sequence is geometric because : (-64)/(-16) = (-16)/(-4)=-4/-1= 4=r
the nth term is : An =A1 × r^(n-1)
a common ratio is : r and A1 the first term
in this exercice : r =4 A1 = 1
An =A1 × r^(n-1)
An =1 × 4^(n-1)=4^(n-1)
Answer:
1 7/8 quarts
Step-by-step explanation:
The amount Yuan has left can be found by multiplying the original amount by the fraction he has left.
__
<h3>used</h3>
After using 1/2 of the broth for soup, the fraction remaining is ...
1 -1/2 = 1/2
The amount Yuan used for gravy is 1/4 of this, or ...
(1/4)(1/2) = 1/8 . . . of the original amount of broth
The total fraction Yuan used was ...
fraction used = fraction for soup + fraction for broth = 1/2 +1/8 = 5/8
<h3>remaining</h3>
Then the fraction remaining is ...
fraction remaining = 1 - fraction used = 1 - 5/8 = 3/8.
The amount remaining is this fraction of the original amount:
(3/8)(5 quarts) = 15/8 quarts = 1 7/8 quarts . . . . remaining
Answer:
C) 4√3
Step-by-step explanation:
The given triangle is an equilateral triangle. BD is angle bisector.
Triangle BCD is a 30-60-90 degree triangle in the ration of 1:√3:2
Here we are given BC, that is highest length of the side.
So 2x = 8
x = 8/2
x = 4.
BD = √3 x
Now plug in x =4, we get
Height (BD) = 4√3
Thank you.
Answer:
You didn't give the expression whose zero you want to find. From the options you wrote, the expression has two zeros, this means it is a quadratic expression.
I will however explain how to find the zero of a quadratic expression.
Step-by-step explanation:
An expression is called quadratic, if the highest degree of the variable is 2, no more, no less. It is of the form: ax² + bx + c, where a, b, and c are constants.
The zeros of a quadratic expression are the values that make the expression vanish, that is equal to zero.
Example: Find the zeros of 2x² - 6x + 4
First, equate the expression to zero
2x² - 6x + 4 = 0
Next, solve for x
2x² - 2x - 4x + 4 = 0
2x(x - 1) - 4(x - 1) = 0
(2x - 4)(x - 1) = 0
(2x - 4) = 0
Or
(x - 1) = 0
2x - 4 = 0
2x = 4
=> x = 4/2 = 2
Or
x - 1 = 0
x = 1
Therefore, the zeros of the polynomial are 1 and 2.